Low-cost smart farming in a shared approach using internet of things and machine learning - Kamlesh Ahuja; Deepika Saxena; Akash Saxena; Chandni Sikarwar; Neeraj Sharma (Institute of Advanced Engineering and Science, 2026)
In this paper, a concept of shared approach of smart farming system is discussed. The technique utilizes the ability of machine learning (ML) and internet of things (IoT) enabled sensors. Additionally, to implement this approach a layered architecture is also proposed. The layered architecture is providing the steps to achieve this model practically by using a cooperative manner. This technique is providing the smart farming services as plug and play basis. Therefore, the complexities of management and implementation is also considered at the billing and maintenance level. Additionally, a conceptual solution for the particular complexity is also suggested. The model can also motivate the new entrepreneurs to adopt the model and serve for the smart farming as service.